IT applications in education and Self-directed learning capacity - La Nhu Hai; Dinh Tran Ngoc Huy; Pham Hung Nhan (Newinera Publisher, 2022)
For differentiated teaching methods in Vietnam, educators only focus on intellectual ability which is provided in academic report cards. Overlooking psychological and cognitive factors leads to poor performance of differentiated teaching in high school in Vietnam. This application of technology in teaching helps teachers to prepare lessons quickly through available lecture templates, and at the same time take advantage of many resources such as videos, images, electronic documents, etc. help attract learners and improve teaching effectiveness.